On the notion of ecological justice - Stefanie Glotzbach (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
The increasing loss of ecosystem services severely affects life perspectives of today's poor and future persons. Thus, governing the use of ecosystem services in an intragenerational and intergenerational just way is an urgent issue. I develop a conception of ecological justice that establishes the specific link between justice and ecosystem services, and argue that specific demands on a conception of ecological justice follow from determining ecosystem services as objects of justice. Showing that Rawls' 'A Theory of Justice' (1971) can consistently meet the identified demands, I verify that it is an appropriate theory for deriving a conception of ecological justice.
Keywords: 330; ecological justice; ecosystem services; global justice; intergenerational justice; environmental ethics.; Umwelt; Gerechtigkeit; Generationenbeziehungen; Rawls-Gerechtigkeitstheorie; Umweltbewusstsein; Theorie